The Impact of Sleep Disorders on Cardiovascular Risk - Blazhkova , Anna; Rehan, Dominka; Rzym , Katarzyna; Solisch, Sven; Susłow, Anna; Szczęsna, Ewa; Szwed, Adam (Journal of Education, Health and Sport, 2025)
Introduction: Sleep disorders are a variety of conditions that disturb the normal sleep-wake cycle. These conditions negatively affect the quality of sleep and the individual’s overall health. These disorders are also associated with high levels of metabolic, neurocognitive, and cardiovascular complications. Given the global prevalence of sleep disorders and cardiovascular disease, understanding their relationship is extremely important given that sleep disorders are increasingly recognized as modifiable risk factors for cardiovascular disease. Purpose of the study: This review examines the relationship between sleep disorders and cardiovascular risk, particularly emphasizing Mechanisms, Outcomes, and Prevention Strategies. Materials and methods: A comprehensive literature review was conducted, analyzing 86 studies from the PubMed database (English-language, up to March 2025) that assess the association between sleep disorders and the risk of cardiovascular disease. Conclusions: Sleep disorders, particularly insomnia and obstructive sleep apnea (OSA), have well-documented associations with increased cardiovascular risk. Evidence supports their role as independent and modifiable contributors to cardiovascular pathophysiology. The mechanisms responsible for their action include autonomic dysregulation, metabolic impairment, endothelial dysfunction, and systemic inflammation. Combining sleep assessment with cardiovascular care, including implementing proven interventions such as cognitive behavioral therapies for insomnia and CPAP therapy for OSA, may be beneficial in reducing morbidity. In addition, addressing determinants of sleep disorders, such as shift work, also seems important. Further research is needed to understand better the association of sleep disorders with cardiovascular risk, to assess long-term treatment effects, and to guide evidence-based integration of sleep medicine with strategies for the prevention and treatment of cardiovascular disease.